Assessment of area specific mineral mixture supplementation on growth and biochemical profile of Jersey crossbred heifers - Kondiba, MA; ., Vipin; Mandal, A; Karunakaran, M (Indian Journal of Dairy Science, 2022)
The present experiment was conducted to assess the effect of area specific mineral mixture (ASMM) supplementation on growth, onset of puberty, blood biochemical and hormonal profiles in Jersey crossbred heifers. Crossbred heifers (n=12) were allocated into two groups (6 in each) namely, control (T0) and treatment (T1) and fed without ASSM and with 30 g of ASMM/heifer/day for a period of four months. In the present study, mean of total body weight gain (42± 4.82 vs. 58.08± 6.42kg) and average daily gain (0.367 ± 0.07 vs. 0.480 ± 0.05 kg/d), plasma calcium (9.63 ± 0.57 vs. 9.85 ± 0.53 mg/dl), phosphorus (5.59 ± 0.33 vs. 5.88 ± 0.35 mg/dl), copper (0.56 ± 0.02 vs. 0.71 ± 0.02 ppm), zinc (0.59 ± 0.01 vs. 0.70 ± 0.02 ppm) and progesterone (0.67 ± 0.02 vs. 0.93 ± 0.06 ng/ml) were significantly lower (P<0.05) in T0 group than T1, while the average values of glucose, NEFA, ±-amino nitrogen level, serum SGOT, serum SGPT, and estradiol-17Î² did not vary significantly (P>0.05) between groups. Significantly (P<0.05) lower age of puberty was observed in the ASMM fed group (20.10±0.13 months) than control (22.12± 0.13 months). It can be concluded that supplementation of ASMM improved growth and the enhanced onset of puberty in crossbred heifers.